Synthesis of β‐SiAlON Nanopowder by Ammonolysis of Alumina–Silica Gel. Issue 1 (28th November 2013) - Zhang, Li; Zhang, Litong; Lin, Zhijun; Jiang, Yan; He, Jing; Cai, Wuji; Li, Siwei; Fuertes, A.
<x xml:space="preserve">Abstract</x> A simple method for synthesis of β‐SiAlON powder by nitridation of alumina–silica gel in ammonia was provided. Precursor was obtained from a mixture of nanosized alumina and colloidal silica. Nitridation reactions took place at 1100°C and conversion to β‐SiAlON was achieved at 1300°C for 2–3 h. The synthesized β‐SiAlON powder was nanocrystalline in size (<100 nm).